Local Budget Transparency and Participation : Evidence from the Kyrgyz Republic - Esenaliev, Damir (World Bank Group, Washington, DC, 2015)
The paper investigates determinants of civic participation in local budget processes in rural areas in the Kyrgyz Republic by using data from the Life in Kyrgyzstan survey, conducted in 2012. The analysis of the data suggests that although civic awareness and interest in local budget processes is relatively high, the participation rate in local budgeting processes is low. The paper also shows that interest, awareness, and participation are positively associated with the age, education, employment, risk-taking attitudes, trust, and social capital of respondents. The paper documents that unawareness and lack of participation are largely related to being female, of non-Kyrgyz ethnic origin, inactive in the labor market, recent internal migrants, and residents of communities with poor infrastructure.